1975
DOI: 10.1038/icb.1975.20
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pre‐partum Milking on the Transfer of Immunoglobulin Into Mammary Secretion of Cows

Abstract: Summary. The significance of local effects associated with mammary involution on transfer of immunojilolmlin and especially on the selective transfer of IgGî nto mammary secretion of cows approaching parturition has been determined. This wa.s carried out by nieasurinfj the chanycs in the eoncentration of I(iG,, IjiC,. IgM and IgA in .serum and manunary .secretion of 5 cows in whicli two mammary glands were milked continuously (twice daily) during the period preceding parturition, while the other two glands wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…In previous studies, prepartum colostrum mass was markedly lower (around 30% compared with the present study; Brandon and Lascelles, 1975;Keller et al, 1977) compared with the results presented here. Selection for higher milk yields over the last decades makes it difficult to dry off modern dairy cows by abrupt first milking at 4 h postcalving, n = 11).…”
Section: Discussionmentioning
confidence: 37%
See 1 more Smart Citation
“…In previous studies, prepartum colostrum mass was markedly lower (around 30% compared with the present study; Brandon and Lascelles, 1975;Keller et al, 1977) compared with the results presented here. Selection for higher milk yields over the last decades makes it difficult to dry off modern dairy cows by abrupt first milking at 4 h postcalving, n = 11).…”
Section: Discussionmentioning
confidence: 37%
“…Milking before parturition is potentially a means of gaining greater IgG concentration and avoiding dilution effects through increased milk secretion (Brandon and Lascelles, 1975;Keller et al, 1977;Greene et al, 1988). In previous studies, half or whole udders of cows or goats were milked prepartum continuously until parturition, which was shown to induce a PRL response in some of the animals, resulting in the initiation of premature lactogenesis (Guy et al, 1994b).…”
Section: Introductionmentioning
confidence: 99%
“…Eckles and Palmer (1916) concluded that heat-coagulable protein content of colostrum is reduced remarkably as DPL was reduced (n 5 4). Negative impacts of CM on IgG and protein content of colostrum have been reported in the literature (Brandon and Lascelles, 1975;Remond et al, 1997b;Rastani et al, 2005). Guy et al (1994) demonstrated that prepartum milking of udder halves resulted in less concentration of IgG 1 in secretions of milked glands than in dry glands from 10 days prepartum to 1 day postpartum.…”
Section: Altered Dry Periodsmentioning
confidence: 93%
“…IgA and IgM are produced locally in the mammary gland, but most of the IgG in mammary secretions is of humoral origin (Lascelles, 1979). The high concentration of IgG 1 is a unique property of colostrum and is selectively transported into the colostrum from the plasma across the blood-milk barrier (Brandon and Lascelles, 1975;Guy et al, 1994). Most likely, this process is controlled locally by neonatal Fc receptor on the acinar epithelial cell (Mayer et al, 2005).…”
Section: Altered Dry Periodsmentioning
confidence: 99%
“…Although the concentration of IgG 1 and IgG 2 in the bovine blood is roughly identical (924.3 and 1330.4 mg/dl respectively; Burton et al., 1991a), IgG1 appears in colostrum in much higher concentration than IgG 2 (50–90 and 1.5–2 g/l respectively; Elfstrand et al., 2002) and the high concentration of IgG 1 is a unique property of colostrum. The IgG class, and IgG1 in particular, is selectively transported from the maternal plasma across the blood–milk barrier into the colostrum as parturition approaches, and this process is controlled locally by MEC (Brandon and Lascelles, 1975; Guy et al., 1994). Most likely, the neonatal Fc receptor on the acinar epithelial cell plays an important role in the IgG transport during colostrogenesis in ruminants (Mayer et al., 2005).…”
Section: Does Dry Period Length Affect Mammary Defence?mentioning
confidence: 99%